Acoustic analysis of Malay /r/ in connected speech: a preliminary study - Wan Ahmad, Wan Aslynn Salwani; Tukiran, Nur Hanisah; Roslan, Muhammad (Universiti Malaya, 2025)
Differences in regional dialects in terms of the productions of consonants and vowels can influence the pronunciation of Standard Malay. This study aims to acoustically characterise the pronunciation of the Malay phoneme /r/, a consonant which has several phonetic variations. A total of 74 words containing the sound were analysed from audio recordings of four Standard Malay-speaking speakers (two males and two females). Acoustic analysis was conducted using Praat, and statistical analysis was performed using SPSS. On average, Standard Malay speakers alternated between producing trill [r] and tap [ɾ] sounds in connected speech, with the /r/ in final position consistently omitted. Acoustically, Standard Malay speakers tended to produce the sound with an F1 value not exceeding 800 Hz and a duration not exceeding 200 ms. These findings have clinical implications for speech-language pathology, particularly in distinguishing typical dialectal variations from speech disorders in Malay speakers. Understanding these patterns can aid in accurate diagnosis and intervention planning for individuals with articulation difficulties.